Routine Use of Tenecteplase for Thrombolysis in Acute Ischemic Stroke. Issue 3 (16th February 2021) - Zhong, Cathy S.; Beharry, James; Salazar, Daniel; Smith, Kelly; Withington, Stephen; Campbell, Bruce C.V.; Wilson, Duncan; Le Heron, Campbell; Mason, Deborah; Duncan, Roderick; Reimers, Jon; Mein-Smith, Frances; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: In ischemic stroke, intravenous tenecteplase is noninferior to alteplase in selected patients and has some practical advantages. Several stroke centers in New Zealand changed to routine off-label intravenous tenecteplase due to improved early recanalization in large vessel occlusion, inconsistent access to thrombectomy within stroke networks, and for consistency in treatment protocols between patients with and without large vessel occlusion. We report the feasibility and safety outcomes in tenecteplase-treated patients. Methods: We performed a retrospective analysis of consecutive patients thrombolyzed with intravenous tenecteplase at 1 comprehensive and 2 regional stroke centers from July 14, 2018, to February 29, 2020. We report the baseline clinical characteristics, rates of symptomatic intracranial hemorrhage, and angioedema. These were then compared with patient outcomes with those treated with intravenous alteplase at 2 other comprehensive stroke centers. Multivariable mixed-effects logistic regression models were performed assessing the association of tenecteplase with symptomatic intracranial hemorrhage and independent outcome (modified Rankin Scale score, 0–2) at day 90. Results: There were 165 patients treated with tenecteplase and 254 with alteplase. Age (75 versus 74 years), sex (56% versus 60% male), National Institutes of Health Stroke Scale scores (8 versus 10), median door-to-needle times (47 versus 48 minutes), or onset-to-needle time (129 versus 130 minutes) were similar between the groups. Symptomatic intracranial hemorrhage occurred in 3 (1.8% [95% CI, 0.4–5.3]) tenecteplase patients compared with 7 (2.7% [95% CI, 1.1–5.7]) alteplase patients ( P =0.75). There were no differences between tenecteplase and alteplase in the rates of angioedema (4 [2.4%; 95% CI, 0.7–6.2] versus 1 [0.4%; 95% CI, 0.01–2.2], P =0.08) or 90-day functional independence (100 [61%] versus 140 [57%], P =0.47), respectively. In mixed-effects logistic regression models, there was no significant association between thrombolytic choice and symptomatic intracranial hemorrhage (odds ratio tenecteplase, 0.62 [95% CI, 0.14–2.80], P =0.53) or functional independence (odds ratio tenecteplase, 1.20 [95% CI, 0.74–1.95], P =0.46). Conclusions: Routine use of tenecteplase for stroke thrombolysis was feasible and had comparable safety profile and outcome to alteplase.